Effect of soybeans from different sources on the quality of high-salt dilute-state soy sauce - LIANG Jinyun, WEN Linfeng, LI Siying, DAI Weijie, CHEN Zhishao, ZHENG Zhongmu, CAO Yong (Zhongguo niangzao)
Using seven kinds of soybean (SB1-SB7) as raw materials, a soy sauce was brewed by high-salt dilute-state technology. The basic physicochemical indexes, free amino acids and free fatty acids composition of the soybean were determined, and the sensory quality, physicochemical indexes, volatile flavor components and non-volatile taste substances of the soy sauce samples were analyzed. The results showed that the physicochemical indexes, free amino acid contents, free fatty acid ratio of 7 different soybeans were different to some extent. SB1, SB2 and SB7 soy sauce samples had better sensory scores (7.86, 7.89 and 8.01 points, respectively). Among them, SB7 soy sauce sample had better comprehensive quality, with higher contents of amino acid nitrogen, reducing sugar and total acid (0.86%, 4.08% and 1.59%, respectively), and the free amino acid and total organic acid contents were highest (30.32 mg/ml and 118.73 mg/ml, respectively). The types of volatile flavor components were the most (50 kinds), and the total contents were the highest (213.2 mg/ml), which was mainly reflected in the higher alcohols and furans (36.86 mg/ml and 11.92 mg/ml, respectively). The sensory score was 8.01, showing the characteristics of delicious and soft, with a strong flavor of sauce and ester.